2020
DOI: 10.1177/0194599820931069
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Consequences of Nonunion in Mandibular and Maxillary Free Flaps

Abstract: Objective To describe the natural history of bone segment union in head and neck free flap procedures and detail the association of poor segment union with postoperative complications. Study Design Case series with chart review. Setting Single tertiary care referral center. Subjects and Method Patients with mandibular or maxillary defects reconstructed with osseous or osteocutaneous free flaps were analyzed (n = 104). Postoperative computed tomography or positron emission tomography/computed tomography scans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…Nevertheless, contact between two graft segments showed significantly faster complete ossification than the contact points between bone graft and original bone. Swendseid et al showed a similar effect, including less dependency on distance between graft segments for complete ossification [ 41 ]. In this context, the data from our multivariate analysis emphasized that radiotherapy as well as the type of bone contact (graft/native vs. graft/graft) showed significantly stronger impacts on ossification and the initial quality of bone contact.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, contact between two graft segments showed significantly faster complete ossification than the contact points between bone graft and original bone. Swendseid et al showed a similar effect, including less dependency on distance between graft segments for complete ossification [ 41 ]. In this context, the data from our multivariate analysis emphasized that radiotherapy as well as the type of bone contact (graft/native vs. graft/graft) showed significantly stronger impacts on ossification and the initial quality of bone contact.…”
Section: Discussionmentioning
confidence: 98%
“…Prior investigations on the integration of native to implanted bone union have been conducted. The mandible warrants special consideration due a unique set of torsional and tension forces acted upon this segment of bone 14,15 . Alterations in masticatory muscles due to resection can cause unbalanced jaw movement, complicating the understanding of forces further 15 .…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies included patients who underwent OCRFFF, they represent a minority of cases. The literature approximates that the rate of nonunion in FFF surgery ranges from 5% to 20% 13–15,19,22,23 . Few investigations have exclusively investigated the degree of bone union in the OCRFFF, but those that have suggest that the rate of nonunion is approximately 2%–5% 2,24–26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations